WASTE NOT, WANT NOT: THE ECO-INITIATIVE EMPOWERING NATUNA'S COMMUNITIES THROUGH SUSTAINABLE PRACTICES - Hanika, Ita; Wulandari, Sri (Jurnal Komunikasi & Media Digital, 2025)
This study explores the initiatives undertaken by the Kehati and Natuna Environmental Community to transform waste into valuable resources. Amidst the growing environmental challenges due to waste accumulation, this community has taken proactive steps to mitigate negative impacts and shift public perception of waste. Employing a qualitative approach, data were gathered through in-depth interviews with the founders of the Kehati Community and participatory observations. Through the diffusion of innovations, the community engaged several district and sub-district parties to implement various innovative programs such as recycling, eco-enzyme production, and transforming waste into eco-bricks and handicrafts. These programs help reduce waste volume and provide economic value to the local community. The study's findings also identify challenges in program development, including limited human resources for marketing recycled products, low youth participation in the community, the public's view that recycled products are sold too expensively, and the need for more intensive education to change public behaviour. The implications of this research highlight the importance of support from the government and related institutions to strengthen and expand waste management programs. Additionally, it underscores the necessity of collaboration between the community, government, and youth to create a more sustainable environment in Natuna.